Hizbut Tahrir: Perjuangan Menegakkan Khilafah (Respon Masyarakat Terhadap Hizbut Tahrir Cabang Jambi) - Sayuti, Sayuti (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2008)
Khilafah is viewed as the most idealform of Governance and leadershipfor islamic society. For almost thirteen centuries, khilafah has united Islamic society whole the world by its glorious institution and civilization progress. The abolishment of khilafah appeared a big protest in whole Islamic world especially from Islamic figures which come from in and outside Turkish who contra of kemal. One of movement which is still exist to struggle for khilafah is Hizbut Tahrir It was established in 1952 in Bait al Maqdis Yerussalem and it was spread in every provinces in Indones ia including Jambi. It works by embracing the public figure, thingking of government side and joining with the intellectuals. However they still thought khilafah is too idealism and hard to realize.